2018
DOI: 10.3329/bjvm.v16i1.37385
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Pathological Effects of Palm, Mustard and Soybean Oils in Rats

Abstract: The investigation was conducted to determine the effects of different edible oils in experimental animals. A total of 36 male Long Evans rats of one month age were randomly divided into four equal groups. Rats of Group A were kept as control by feeding rat pellet. Rats of Group B, C and D were fed rat pellet by mixing of palm, mustard and soybean oils respectively, at the dose of 15 % in feed for 6 months. The methods included determination of weight gains, lipid profiles and histopathological lesions in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Supplementation of ghee and dalda increased total serum cholesterol significantly in this study. These results agreed with findings reported that palm and soybean oil (Hoque et al, 2018), high level of fish oil or fat in diet (Garg and Blake, 1997) increased the concentration of serum cholesterol. This result is also similar to Jeffery et al (1996) observed that the serum total cholesterol concentrations raised in the animals fed the high-fat diets.…”
Section: Discussionsupporting
confidence: 93%
“…Supplementation of ghee and dalda increased total serum cholesterol significantly in this study. These results agreed with findings reported that palm and soybean oil (Hoque et al, 2018), high level of fish oil or fat in diet (Garg and Blake, 1997) increased the concentration of serum cholesterol. This result is also similar to Jeffery et al (1996) observed that the serum total cholesterol concentrations raised in the animals fed the high-fat diets.…”
Section: Discussionsupporting
confidence: 93%